CHP1 promotes lipid droplet growth and regulates the localization of key enzymes for triacylglycerol synthesis - Guang Yang; Ximing Du; Dougall Norris; Armella Zadoorian; Yuyuan Zheng; Mingming Gao; Andrew J. Brown; Shane T. Grey; Chun Zhou; Hongyuan Yang (Proceedings of the National Academy of Sciences, 2025)
The glycerol-3-phosphate (G-3-P) pathway is central to the synthesis of triacylglycerols (TAGs) and glycerophospholipids, essential for membrane biogenesis and lipid storage. The first and rate-limiting step in this pathway is catalyzed by glycerol-3-phosphate acyltransferases (GPATs), with microsomal GPAT3 and GPAT4 being evolutionarily conserved and predominant in most tissues. While previous studies have implicated Calcineurin B homologous protein 1 (CHP1) as a cofactor for GPAT4, the broader role of CHP1 in regulating microsomal GPATs and TAG biosynthesis remains unclear. Here, we demonstrate that CHP1 is a critical regulator of both GPAT3 and GPAT4, essential for their stability, enzymatic activity, and lipid droplet (LD) localization. Structural modeling and mutational analyses identified key hydrophobic interfaces mediating the CHP1–GPAT interaction, which are required for optimal GPAT activity and LD growth. Loss of CHP1 impairs LD expansion and disrupts the localization of GPAT3/4 and downstream enzymes in the TAG synthesis pathway, including 1-acylglycerol-3-phosphate O-acyltransferase 3 (AGPAT3) and diacylglycerol O-acyltransferase 2 (DGAT2). Mechanistically, CHP1 helps circumvent seipin-mediated restriction of late LD-targeting enzymes, facilitating their access to mature LDs. Together, our findings reveal CHP1 as a dual-function regulator that stabilizes and activates microsomal GPATs while enabling the coordinated recruitment of TAG biosynthetic enzymes to LDs. This work uncovers a previously unrecognized mechanism for regulating LD growth and glycerolipid metabolism, with broad implications for lipid homeostasis and metabolic diseases.